1988
DOI: 10.1093/nar/16.13.6085
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the contribution of sequence motifs within the IgH enhancer to tissue specific transcriptional activation

Abstract: We have investigated the role of sequence motifs in the immunoglobulin heavy chain (IgH) enhancer on its activity in myeloma and fibroblast cell-lines. In transient transfection assays the transcription stimulatory activity of the enhancer is decreased in myeloma cells by mutating the E motifs 1, 2 and 3, the core motifs C1, C2, C3 and the octamer motif (OC) and in fibroblasts by mutating E2, E3, and C2. Our results suggest that transcription factors binding to E1, C1, C3 and OC contribute in a positive manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…The E2 and E5 motifs are important E-protein binding sites found in the regulatory regions of many immune function genes, including those encoding the Igs (17)(18)(19)(20). Although knockout studies in mice indicate that E2A is an essential factor for lymphocyte development, other E-proteins (e.g., HEB) are able to compensate to a substantial degree for the lack of E2A when expressed in an appropriate context, i.e., as knockin mutants under the control of the E2A promoter (21).…”
mentioning
confidence: 99%
“…The E2 and E5 motifs are important E-protein binding sites found in the regulatory regions of many immune function genes, including those encoding the Igs (17)(18)(19)(20). Although knockout studies in mice indicate that E2A is an essential factor for lymphocyte development, other E-proteins (e.g., HEB) are able to compensate to a substantial degree for the lack of E2A when expressed in an appropriate context, i.e., as knockin mutants under the control of the E2A promoter (21).…”
mentioning
confidence: 99%
“…The E2 to E5 motifs contain a consensus CANNTG motif that binds the basic helix-loop-helix (bHLH) family of transcription factors (12,17). Mutational analysis of E motifs has shown that loss of single elements does not significantly affect enhancer activity (13,15,23,35). This observation has been interpreted to indicate that there is redundancy among the E elements; that is, absence of one E element can be functionally compensated for by other E elements present in the enhancer.…”
mentioning
confidence: 99%
“…Two others, octamer (referring to the conserved octanucleotide ATGCAAAT; Singh et al 1986;Staudt et al 1986) and ~EBP-E , were defined first by in vitro binding assays. Deletions or mutations of these sites generally reduce overall enhancer activity (Lenardo et al 1987;Kiledjian et al 1988;Perez-Mutul et al 1988;Tsao et al 1988). Even though activity of the enhancer is restricted to B cells, only one of these sites (octamer) is known to bind B-cell-specific proteins (OTF-2/oct-2, OTF-2b; Landolfi et al 1986;Staudt et al 1986;Gerster IPresent address: Cold Spring Harbor Laboratory, Cold Spring Harbor, New York 11 ;'24 USA.…”
mentioning
confidence: 99%
“…Studies of mutant enhancers have indicated that this site alone may be responsible for as much as 30% of the enhancer's activity in B cells (Lenardo et al 1987;Kiledjian et al 1988;Perez-Mutul et al 1988;Tsao et al 1988). The site was also shown to contribute to the low level of enhancer activity observed in non-B cells (Kiledjian et al 1988).…”
mentioning
confidence: 99%